2014
DOI: 10.1186/1756-0500-7-187
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of mutated BRAF signaling modulates thyroid cancer phenotype

Abstract: BackgroundThyroid cancer is the most common endocrine-related cancer in the United States and its incidence is rising rapidly. Since among various genetic lesions identified in thyroid cancer, the BRAFV600E mutation is found in 50% of papillary thyroid cancers and 25% of anaplastic thyroid cancers, this mutation provides an opportunity for targeted drug therapy. Our laboratory evaluated cellular phenotypic effects in response to treatment with PLX4032, a BRAFV600E-specific inhibitor, in normal BRAF-wild-type t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Vemurafenib binds selectively to the active site of BRAFV600E protein, which differs in conformation from wild-type BRAF, and inhibits downstream MAPK signaling [ 7 ]. Short-term treatment with BRAFV600E inhibitors has drastic anti-proliferative effects on mutated thyroid cancer cells including induction of apoptosis [ 8 - 10 ]. The drug vemurafenib has also recently proved to be useful in treating advanced thyroid cancer patients in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Vemurafenib binds selectively to the active site of BRAFV600E protein, which differs in conformation from wild-type BRAF, and inhibits downstream MAPK signaling [ 7 ]. Short-term treatment with BRAFV600E inhibitors has drastic anti-proliferative effects on mutated thyroid cancer cells including induction of apoptosis [ 8 - 10 ]. The drug vemurafenib has also recently proved to be useful in treating advanced thyroid cancer patients in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Since development of resistance appeared to be mediated through mechanisms involved in ERK signaling, we analyzed expression of key effector molecules, ERK and mTOR. We noted inhibition of phosphorylation of these molecules in normal BCPAP cells in response to 24 hour VMR treatment in a previous study [ 16 ]. When comparing expression levels of phosphorylated signaling proteins among cell lines, we found that the resistant BCPAP cells expressed a remarkably higher amount of phospho-ERK compared to normal BCPAP (Figure 4 ).…”
Section: Resultsmentioning
confidence: 69%
“…Presence of the BRAFV600E mutation has been correlated with recurrence, resistance to radioiodine, and increased mortality [ 3 , 10 13 ]. Inhibition of BRAFV600E kinase with VMR within thyroid cancer cells has been shown to inhibit cell proliferation and induce apoptosis [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, interleukin-1 has dual roles of anti-tumor and pro-tumor [43]. Positive regulation of MAP kinase activity and metalloendopeptidase activity are thought to be associated with thyroid cancer [44,45]. This is a validation of the major carcinogenic event of PTC is the activation of MAPK.…”
Section: Discussionmentioning
confidence: 99%